Handling of Umrah Packages by Tour Leader at PT Bintang Wisata in Makassar: Penanganan Paket Umrah oleh Tour Leader Pada PT Bintang Wisata Di Makassar - Oemardany Aldevis Masran; Muhammad Yusuf; Margaretha Wadid Rante (Politeknik Pariwisata Makassar, 2024)
This research aims: (1) To determine the standard operating procedure for handling Umrah pilgrims by Tour Leaders at PT. Bintang Wisata Makassar. (2) Inhibiting Factors in Handling Umrah Pilgrims by Tour Leaders at PT. Bintang Wisata Makassar. This research collected data using interviews and documentation techniques at PT. Bintang Wisata Makassar. Data analysis was carried out using qualitative descriptive methods. The results of this research show how the procedures for handling Umrah pilgrims by Tour Leaders at PT. Bintang Wisata Makassar. Handling of Umrah Pilgrims by Tour Leader at PT. Bintang Wisata Makassar is still lacking in handling Umrah pilgrims from the start of the trip to the end of the journey and is not entirely by the standard operational procedures that PT. Bintang Wsata Makassar has set. The problem that tour leaders often encounter while traveling is during the In Tour or carrying out the Umrah pilgrimage, where much time is wasted because there is no preparation or solution from the tour leader before starting the trip handling Umrah pilgrims. PT. Bintang Wisata Makassar uses Tour Leaders registered with the Indonesian Tourist Guide Association (HPI) organization and, of course, have a license or certificate of expertise as guides fit into the field. Still, when researched, Tour Leaders were sometimes found to have made mistakes the first time they handled it. Umrah pilgrims, so Tour Leaders need to add insight and research. So, when a Tour Leader needs to correct a mistake in handling the Umrah pilgrims, the Tour Leader can provide an excellent solution to the Umrah pilgrims.